POTRET PENGARUSUTAMAAN GENDER DALAM KEHIDUPAN KELUARGA BATAK TOBA DI TAPANULI UTARA - Harisan Boni Firmando (Jurnal Ilmiah Sosiologi Agama (JISA), 2020)
The fact is that the patrilineal kinship system and the customs of the Toba Batak people are often misunderstood, interpreted and used as the basis that the Toba Batak ethnicity is anti-gender. Though all of that is baseless especially if it refers to a true understanding of the information about the kinship system and how the Batak Toba tribal customs treat women. Ideally the Toba Batak tribe elevates the degree of women which can be seen in the noble values of local wisdom and the daily life of the Toba Batak people.The method used in this study is a qualitative method, to understand phenomena about what is experienced by research subjects holistically, by describing words and language, in a special natural context and by utilizing various natural methods. This study was conducted in two districts namely Sipoholon and Tarutung Districts.This article emphasizes the portrait of gender mainstreaming in the life of the Toba Batak family. There are strong indications of the Toba Batak tribe in the local wisdom values strategy that strives to uphold women's degrees and uphold gender equality. In dialoguing the case, gender is used as the knife of analysis and sociology as the approach